Lakes as Source of Cholera Outbreaks, Democratic Republic of Congo - Didier Bompangue (Emerging Infectious Diseases, 2008)
We studied the epidemiology of cholera in Katanga and Eastern Kasai, in the Democratic Republic of Congo, by compiling a database including all cases recorded from 2000 through 2005. Results show that lakes were the sources of outbreaks and demonstrate the inadequacy of the strategy used to combat cholera.